Structure and function of carbonic anhydrases - Supuran, Claudiu T (Biochemical journal, 2016)
Carbonic anhydrases (CAs, EC 4.2.1.1) catalyse the interconversion between CO2 and bicarbonate as well as other hydrolytic reactions. Among the six genetic families known to date, the α-, β-, γ-, δ-, ζ- and η-CAs, detailed kinetic and X-ray crystallographic studies have allowed a deep understanding of the structure-function relationship in this superfamily of proteins. A metal hydroxide nucleophilic species of the enzyme, and a unique active site architecture, with half of it hydrophilic and the opposing part hydrophobic, allow these enzymes to act as some of the most effective catalysts known in Nature. The CA activation and inhibition mechanisms are also known in detail, with a large number of new inhibitor classes being described in the last years. Apart from the zinc binders, some classes of inhibitors anchor to the metal ion coordinated nucleophile, others occlude the entrance of the active site cavity and more recently, compounds binding outside the active site were described. CA inhibition has therapeutic applications for drugs acting as diuretics, antiepileptics, antiglaucoma, antiobesity and antitumour agents. Targeting such enzymes from pathogens may lead to novel anti-infectives. Successful structure-based drug design campaigns allowed the discovery of highly isoform selective CA inhibitors (CAIs), which may lead to a new generation of drugs targeting these widespread enzymes. The use of CAs in CO2 capture processes for mitigating the global temperature rise has also been investigated more recently.